2004
DOI: 10.4049/jimmunol.173.4.2241
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Prolonged Antigen Presentation after Herpes Simplex Virus-1 Skin Infection

Abstract: It has been reported that MHC class I-restricted Ag presentation persists for only a short period following infection with certain pathogens, declining in parallel with the emergence of specific CTL activity. We have examined this issue in the case of murine infection with HSV-1. We found that the period of Ag presentation capable of priming naive CD8+ T cells is comparatively prolonged, persisting for at least 7 days after infection, and continuing despite the appearance of localized CTL activity. Ag presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 19 publications
4
56
1
Order By: Relevance
“…It is possible that Ag ligand persistence sufficient to drive or help previously stimulated T cells may be important to support the long-lasting effector responses we observe, but insufficient to drive induction of the naive OT-1 T cells used in the assay. Other recent studies have shown that for maximal CTL induction, a short period of stimulation (24 h), not prolonged Ag presentation, is required (52,64). These studies suggest that the magnitude and duration of CD8 T cell responses are determined by the initial clonal burst of T cell activation resulting from an initial period of engagement with APCs.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is possible that Ag ligand persistence sufficient to drive or help previously stimulated T cells may be important to support the long-lasting effector responses we observe, but insufficient to drive induction of the naive OT-1 T cells used in the assay. Other recent studies have shown that for maximal CTL induction, a short period of stimulation (24 h), not prolonged Ag presentation, is required (52,64). These studies suggest that the magnitude and duration of CD8 T cell responses are determined by the initial clonal burst of T cell activation resulting from an initial period of engagement with APCs.…”
Section: Discussionmentioning
confidence: 74%
“…The in vivo Ag presentation assay was performed as previously described (52). Briefly, mice were injected in the footpad with 500,000 DCs that were transduced with lvv expressing OVA or pulsed with SIINFEKL peptide or OVA protein as indicated.…”
Section: In Vivo Ag Presentation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This process leads to 0.5% diversity of the memory repertoire, because 0.58 10 ≈ 0.5%. In vivo T cell tracking experiments have shown that T cells continue to interact with antigen in the lymph node up to 5 days after initial stimulation [41,42], and examinations of draining lymph nodes have found that antigen capable of priming naive T cells is present up to 7 days post inoculation [43], both of which support the concept that the selection process may continue during each T cell division. Although the exact mechanism of the T cell expansion during the primary immune response remains elusive, it is observed that the expansion of the T cells is nonlinear [44], and that in most cases there is competition among the T cells for the presented antigen [45,46].…”
Section: Tcr Selection Dynamicsmentioning
confidence: 82%
“…It has been suggested that extended interaction between APCs and T cells is required to elicit fit T cells that can respond to homeostasis cytokines for survival [70][71][72] . In addition, prolonged Ag presentation might be required to have sufficient time for all possible cognate T cells to be screened by Ag presenting APCs and induce maximal CTL responses 73 . Furthermore, it has recently been demonstrated that Ag presentation in the late stage of viral infection may be needed to generate memory CD4 and CD8 T cell responses [74][75][76] .…”
Section: Prolongedmentioning
confidence: 99%